Analisis Dinamik Struktur Kolom Kantilever dan Portal di Ponton sebagai Simulasi Turbin Angin Terapung dan Rumah Terapung terhadap Gelombang - Patria Kusumaningrum; Anggito Tri Agastya; Olivia Debora Papuani Tambunan (MEDIA KOMUNIKASI TEKNIK SIPIL, 2025)
Floating wind turbines and floating houses are innovative solutions to global challenges such as land scarcity and rising sea levels. This study investigates the dynamic responses of both structures under wave excitation. The floating wind turbine is modeled as a cantilever column with a lumped mass at the top, while the floating house is idealized as a single-story portal frame. Both structures are supported by pontoons, which are represented as beams on elastic foundations using the Winkler foundation theory. Wave loads are modeled based on linear wave theory and Froude-Krylov forces. The analysis is conducted in the time domain using the Finite Element Method and Newmark-Beta integration scheme. The results show that the floating wind turbine experiences a maximum drift of 61.986 mm, heave of 104.310 mm, and pitch of 0.141°, whereas the floating house experiences a maximum drift of 35.587 mm, heave of 60.621 mm, and pitch of 0.408°. The highest internal forces occur in the pontoon section of both structures, indicating that the pontoon plays a significant role in resisting wave loads. This study contributes to a better understanding of the dynamic behavior of floating structures and demonstrates that a simplified 2D modeling approach can be effectively used as an initial step in designing stable and efficient floating systems.